Copolymers from norbornene and norbornadiene with organized morphologies and high T-g values obtained via ROMP with a highly reactive [RuCl3(PCy3)(2)] complex - Ferraz, C. P.; Fonseca, L. R.; Tomazetti, V.; Silva, F. C. S.; Lima-Neto, B. S.; Carvalho, V. P. [UNESP] (Royal Soc Chemistry, 2016)
The [RuCl3(PCy3)(2)] complex presented high reactivity toward ring opening metathesis polymerization (ROMP) of norbornadiene (NBD) in a non-degassed solution upon addition of ethyl diazoacetate (EDA). Quantitative yields of polyNBD were obtained instantaneously at 25 degrees C. ROMP of norbornene (NBE) occurred better at 50 degrees C for 60 min, with 95% of isolated polyNBE. Copolymers with different porous structures were obtained from ROMP of NBE in the presence of NBD with different starting [NBE]/[NBD] molar ratios at 25 degrees C. SEM micrographs showed a more organized porous structure as the NBD loading decreased. A well-defined honeycomb-like pattern was recorded for the copolymer from the run with an NBE: NBD molar ratio load of 5000: 500. The T-g values varied from 37 degrees C in polyNBE to 90 degrees C in poly[NBE-co-NBD] as the NBD loading increased.